Hydrolysis of Phosphatidylinositol 4,5-Bisphosphate Mediates Calcium-induced Inactivation of TRPV6 Channels - Thyagarajan, Baskaran (American Society for Biochemistry and Molecular Biology, 2008)
TRPV6 is a member of the transient receptor potential superfamily of ion channels that facilitates Ca(2+) absorption in the intestines. These channels display high selectivity for Ca(2+), but in the absence of divalent cations they also conduct monovalent ions. TRPV6 channels have been shown to be inactivated by increased cytoplasmic Ca(2+) concentrations. Here we studied the mechanism of this Ca(2+)-induced inactivation. Monovalent currents through TRPV6 substantially decreased after a 40-s application of Ca(2+), but not Ba(2+). We also show that Ca(2+), but not Ba(2+), influx via TRPV6 induces depletion of phosphatidylinositol 4,5-bisphosphate (PI(4,5)P(2) or PIP(2)) and the formation of inositol 1,4,5-trisphosphate. Dialysis of DiC(8) PI(4,5)P(2) through the patch pipette inhibited Ca(2+)-dependent inactivation of TRPV6 currents in whole-cell patch clamp experiments. PI(4,5)P(2) also activated TRPV6 currents in excised patches. PI(4)P, the precursor of PI(4,5)P(2), neither activated TRPV6 in excised patches nor had any effect on Ca(2+)-induced inactivation in whole-cell experiments. Conversion of PI(4,5)P(2) to PI(4)P by a rapamycin-inducible PI(4,5)P(2) 5-phosphatase inhibited TRPV6 currents in whole-cell experiments. Inhibiting phosphatidylinositol 4 kinases with wortmannin decreased TRPV6 currents and Ca(2+) entry into TRPV6-expressing cells. We propose that Ca(2+) influx through TRPV6 activates phospholipase C and the resulting depletion of PI(4,5)P(2) contributes to the inactivation of TRPV6.